Perancangan Aplikasi Kas Pintar (AKAPI) Berbasis Website Pada Yayasan Yatim Impian - Esti Febriyanti; Melliana Fransiska; Ina Maryani (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
AKAPI is a website-based application to help manage finances at the Yatim Impian Foundation. AKAPI is the result of community service activities carried out in five stages. It starts with the preparation stage, assessment, then planning, then the implementation of programs and activities, and ends with the evaluation stage. Manual financial recording, which has been carried out by the Foundation, has the risk of loss or input errors. In addition, the website that has been managed does not yet have financial management features so the Treasurer is quite difficult in managing finances. Therefore, AKAPI is expected to make the Foundation's financial management more effective and efficient, and can help support the work and development of the Foundation.